Manajemen Keuangan Bisnis Untuk Meningkatkan Potensi Profit UMKM - Sev Rahmiyanti; Fiorenza Rafa Talitha Sevandra; Achmad Rifai; Rizal Zulkarnain; Gilang Ganjar Amrih; Dwi Fitri Ningsih; Achmad Fauzi; Frida Tri Meidina (Jurnal Abdi Masyarakat Nusantara, 2026)
Financial management of business is a crucial factor in ensuring business continuity and sustainability, particularly for micro and small enterprises that often face limited resources. Financial management involves not only capital planning, cash flow control, expenditure management, and transaction recording, but also requires discipline and courage in conducting supervision to balance business needs with household demands. This study aims to explain the concept of business financial management through three main stages, namely planning, implementation, and control, as well as to analyze the strategic benefits of financial recording and monitoring for business sustainability. The method employed is a literature review and conceptual descriptive analysis based on the theoretical framework of financial management for small businesses. The results indicate that disciplined financial recording provides accurate information about business conditions, prevents bankruptcy, maintains continuity, and supports the improvement of family welfare. Thus, structured financial management plays a pivotal role not only in sustaining business operations but also in building a foundation for healthy, secure, and sustainable business growth.